PRODUCTION OF 2-PHENYLETHANOL IN THE BIOTRANSFORMATION OF CINNAMYL ALCOHOL BY THE PLANT PATHOGENIC FUNGUS Colletotrichum acutatum - VELASCO B., Rodrigo; GIL G., Jesús H.; GARCÍA P., Carlos M.; DURANGO R., Diego L. (Vitae, 2010)
Biocatalytic processes may offer a cheaper alternative to natural production of flavours. The biotransformation of cinnamyl alcohol is investigated using the plant pathogenic fungus Colletotrichum acutatum as a biocatalyst. Results show that substrate is converted to 3-phenyl-1-propanol, 1-phenyl-1,3- propanediol, 2-phenylethanol, 1-phenyl-1,2-ethanediol, 3-phenyl propyl acetate, and hydrocinnamic acid. The structures of the metabolic products are elucidated on the basis of their spectral data. 2-phenylethanol has a sweet, floral odor and a wide variety of applications, especially, for the perfume and food industries. A time-course experiment demonstrates that 2-phenylethanol appeared after 120 hours, reaching almost 8% of relative abundance. Additionally, the influence that the culture broth has on the conversion capacity is investigated. It has been discovered that cinnamyl alcohol is converted faster when the substrate is incorporated in a Sabouraud medium; under this condition, 2-phenylethanol is the most common product after 288 hours reaching about 90% of the relative abundance. Biotransformation of cinnamyl alcohol using C. acutatum in a Sabouraud medium can offer a simple and efficient way to obtain 2-phenylethanol with high yield.